Exploring the Determinants of Antenatal Care Services Uptake: A Qualitative Study among Women in a Rural Community in Northern Ghana - Gilbert Ti-enkawol Nachinab; Charles Ampong Adjei; Florence Assibi Ziba; Richard Asamoah; Priscilla Adumoah Attafuah (Hindawi Limited, 2019)
Background. Global evidence has shown significant contribution of Antenatal care (ANC) in the detection and treatment of pregnancy related complications. Over the years, many areas in Ghana have recorded high uptake of ANC. However, this is not the case for Binduri district in Northern Ghana where only 37.4% of pregnant women utilised the services of ANC during their period of pregnancy compared to a national figure of 87%. We therefore sought to explore the determinants of ANC uptake among women who failed to utilise ANC services during their period of pregnancy in Binduri District in Northern Ghana. Methodology. The study was an exploratory descriptive study using purposive sampling technique. A total of 15 women who met the inclusion criteria for the study were recruited for a face-to-face interview. The data were analysed using the procedure of inductive thematic analysis. Results. The study findings showed that several factors hindered the use of ANC among our participants. The individual factors that were responsible for nonutilisation of ANC included financial constraints hindering registration with the national health insurance scheme, excuses of being busy, perception that pregnancy was not sickness and concentration on work. Perceived poor attitude of nurses was the only health system factor that contributed to non utilisation of ANC services. Conclusion. There is the need for establishment of registration centres of the national health insurance in all communities to make the scheme more accessible. There should also be intensive public education on importance of attending ANC.